Proteomic analysis of native cerebellar iFGF14 complexes. Issue 4 (3rd July 2016) - Bosch, Marie K.; Nerbonne, Jeanne M.; Townsend, R. Reid; Miyazaki, Haruko; Nukina, Nobuyuki; Ornitz, David M.; Marionneau, Céline
ABSTRACT: Intracellular Fibroblast Growth Factor 14 (iFGF14) and the other intracellular FGFs (iFGF11-13) regulate the properties and densities of voltage-gated neuronal and cardiac Na + (Nav) channels. Recent studies have demonstrated that the iFGFs can also regulate native voltage-gated Ca 2+ (Cav) channels. In the present study, a mass spectrometry (MS)-based proteomic approach was used to identify the components of native cerebellar iFGF14 complexes. Using an anti-iFGF14 antibody, native iFGF14 complexes were immunoprecipitated from wild type adult mouse cerebellum. Parallel control experiments were performed on cerebellar proteins isolated from mice ( Fgf14 −/− ) harboring a targeted disruption of the Fgf14 locus. MS analyses of immunoprecipitated proteins demonstrated that the vast majority of proteins identified in native cerebellar iFGF14 complexes are Nav channel pore-forming (α) subunits or proteins previously reported to interact with Nav α subunits. In contrast, no Cav channel α or accessory subunits were revealed in cerebellar iFGF14 immunoprecipitates. Additional experiments were completed using an anti-PanNav antibody to immunoprecipitate Nav channel complexes from wild type and Fgf14 −/− mouse cerebellum. Western blot and MS analyses revealed that the loss of iFGF14 does not measurably affect the protein composition or the relative abundance of Nav channel interacting proteins in native adult mouse cerebellar Nav channel complexes.